Implementing basal reading program in EFL upper secondary school settings - Sajidin; Mulyadi, Dodi; Robiasih, Hasti (Universitas Muhammadiyah Sidoarjo, 2021)
Basal readers have been selected by the school to cope with students’ lack of vocabulary size. With some positively perceived learning outcomes, the readers continued to be used from year to year and were decided as a school program, in addition to ELT national curriculum. The research is aimed at exploring the following aspects: (1) the teacher’s use of basal readers in the classrooms, (2) the classroom procedures developed by the teacher understudy, and (3) the students’ response to the implementation of the basal reading program. A descriptive case study with classroom observation as a main data collection technique was employed to explore the phenomena. The research brings several points to consider. First, basal readers have been extensively used by the school for different purposes: 1) for vocabulary enrichment, (2) for intensive reading materials, (3) as resource making classroom tests, and (4) a basis for writing phonetic symbols, and (5) for promoting speaking skills. Second, the school has developed its own strategies to use the readers with specific procedures. Third, the use of basal readers was positively responded to by the students with some suggestions for better implementation. HIGHLIGHTS: Basal reading program was implemented with a specific procedure developed by the local school English teachers. Basal readers selected for the reading program were utilized to develop reading skills in which vocabulary memorization and pronunciation drills were used to support the skills. The program was positively responded by the students with some suggestions for a better implementation.